Predictive markers of rapid disease progression and chemotherapy resistance in triple-negative breast cancer patients following postoperative adjuvant therapy - Tao Ma; Xiao-meng Hao; Hong-dan Chen; Min-hui Zheng; Xiao-geng Chen; Shuang-Long Cai; Jin Zhang (Scientific Reports)
Abstract Triple-negative breast cancer (TNBC) is a diverse category with a subset that displays particularly aggressive characteristics, referred to in this study as “rapid relapse” TNBC (rrTNBC). This term is defined as the occurrence of distant metastasis or death within 24 months post-diagnosis. The paper mainly studies the clinicopathologic traits of TNBC patients experiencing rapid disease progression and chemotherapy resistance and identify predictive markers for this outcome. A retrospective evaluation was conducted on 2294 TNBC patients who underwent surgery at Tianjin Medical University Cancer Hospital. Of these, 369 were categorized as experiencing rapid relapse, while 1925 did not relapse rapidly. Logistic regression analysis was applied to determine potential markers predictive of rapid relapse post-chemotherapy. Both univariate and multivariate logistic regression analyses pinpointed several predictors of rapid relapse in TNBC patients post-chemotherapy. These include age at diagnosis (≥ 50 years, OR = 0.413, 95% CI: 0.289–0.590), postoperative pathological T staging (T2, OR = 2.557, 95% CI: 1.766–3.703; T3 + T4, OR = 3.725, 95% CI: 1.355–10.454), and N staging (N1, OR = 3.056, 95% CI: 2.021–4.619; N2, OR = 6.917, 95% CI: 3.920–12.206; N3, OR = 24.597, 95% CI: 11.875–50.948). Additionally, sTIL expression (intermediate, OR = 0.204, 95% CI: 0.139–0.300; high, OR = 0.020, 95% CI: 0.011–0.035) and Her2 expression (Her2 1+, OR = 0.470, 95% CI: 0.321–0.688) were identified as protective indicators against rapid relapse. A predictive model incorporating these predictors yielded a C-index of 0.898 in the training set and 0.938 in the validation set, with respective Brier scores of 0.079 and 0.073. The study successfully established and validated a predictive model for rapid disease progression and chemotherapy resistance in TNBC patients post-chemotherapy, demonstrating robust discrimination and accuracy.